TINGKAT PENGETAHUAN KESEHATAN REPRODUKSI PADA SISWA SMA KANJENG SEPUH GRESIK - Wiwik Afridah; Ratna Fajariana (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
ABSTRACTBackground: Adolescence is a transitional period between the time of children with adulthood. There are stillmany found little regard for teens on health on reproductive, will consequently risk against the occurrence ofan increase in diseases, among others; Sexually Transmitted Infections (STI). Methods: This type of researchis the pre-design experiments using One-Shot Case Study, measured through a questionnaire. Class X studentpopulation of 33 students, XI IPS 2 of 26 students, and XII IPS 1 of 29 students. With a variable level ofknowledge about reproductive health education, sexually transmitted diseases, prevention and theintroduction of infectious disease symptoms, processed and analyzed using descriptive statistics. Results: Theresults of the research on reproductive health education on class X most (63, 64%) have moderate levels ofknowledge about sexually transmitted diseases in class XI IPS 2 most (73%), 8 have a level of knowledge,level of knowledge about the prevention of infectious diseases and the introduction at the XII 1st most IPS(58, 62%) have moderate levels of knowledge. Conclusion: the level of knowledge of students of SMKKanjeng Sepuh Gresik about adolescent reproductive health is on a category of being. Therefore the expectedreproductive and Sexual health education as a subject/local content through the media of the school as aproper step as a medium of education can provide information on sexual and reproductive health is right forteens.